Conformal and Probabilistic Prediction with Applications 5th International Symposium, COPA 2016, Madrid, Spain, April 20-22, 2016, Proceedings - Gammerman, Alexander; Luo, Zhiyuan; Vega, Jesús; Vovk, Vladimir (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the refereed proceedings of the 5th International Symposium on Conformal and Probabilistic Prediction with Applications, COPA 2016, held in Madrid, Spain, in April 2016. The 14 revised full papers presented together with 1 invited paper were carefully reviewed and selected from 23 submissions and cover topics on theory of conformal prediction; applications of conformal prediction; and machine learning.